Management of Antiepileptic Treatment After Epilepsy Surgery - Practices and Problems - Rubboli, Guido; Sabers, Anne; Uldall, Peter; Malmgren, Kristina (Current Pharmaceutical Design, 2017)
Background: Although epilepsy surgery is a recognized treatment option for drug-resistant epilepsies since several decades, the management of antiepileptic drugs (AEDs) after successful surgery still remains one of the most difficult and unsolved therapeutic challenges. Indeed, no systematic controlled trials have been specifically conducted so far and no consensus or standardized guidelines regarding postsurgical drug discontinuation policy and procedures are available. Methods: In this paper, we aim to provide an updated overview on the present knowledge on this topic, which is based mainly on retrospective studies reporting practices used in individual centers. Results: Currently available data suggest that: 1) rate of seizure recurrence appears to be higher in patients undergoing early (before 6 months or 9 months according to different studies) AED withdrawal; 2) seizures that recur during AED tapering are easier to control than unprovoked postoperative seizure relapses; 3) there is no evidence to support negative long-term implications on seizure outcomes in patients who attempted AED withdrawal. In the pediatric age group, shorter intervals from surgery to AED reduction and to complete AED discontinuation predict seizure relapse during or after AED reduction/withdrawal. However, this does not correlate with the chances of regaining seizure freedom after drug reintroduction. Conclusion: Carefully conducted prospective longitudinal studies and randomized controlled trials are warranted to establish the correct post-surgical pharmacologic treatment and to identify the best candidates for AEDs discontinuation.
Keywords: drug resistance